Effect of hanging white bedsheet around phototherapy unit on TSB level in neonatal jaundice: a comparative study - Chong, Li Tsu; Lee, Shalin Wan Fei; Chan, Kim Geok; Saloma Pawi; Feryante Rintika; Drina Dalie (Malaysian Journal of Medicine and Health Sciences, 2020)
Introduction: Vaping is a use of electronic devices which do not produce smoke or steam, rather an aerosol consisting of fine particles, containing varying amounts of propylene glycol, glycerine, flavourings and other chemicals. It is battery-powered devices that mimic the action of smoking. In Malaysia, vaping has become a major trend. Videos are going viral on social media showing school students in uniform proudly puffing away. The aim of this study was to find out the acceptance of vaping among medical and nursing students. Methods: A descriptive cross-sectional study with multiple stage of sampling technique on population of 624 medical and nursing students. Total samples were 389, by Krejci Morgan (1970) sampling technique. Structured questionnaires by A. Gorukanti (2018) with 15 items consisted of knowledge, attitude and acceptance and attitude and believe as data collection tools. Results: Re¬sults showed 9% to 10% of respondents are still smoking, they believed e- cigarette is safe and would not affect one’s health, as it is a water-based product trademarked. They also regard e-cigarette a way of quitting or cutting down smoking. Conclusion: 10% of respondents consistently believed e-cigarettes is harmless. Although the percentage may look small but the impact on the public is huge. However, 90% strongly agreed e-cigarettes ‘vapour is dan¬gerous to babies and kids. What concerns us is the consistent group of the 10%, are students who will become our healthcare providers in the future. Their strong-belief in vaping will influence the future of the public understanding, “If doctors and nurses said vaping is safe ... it is safe… right? why not. which is harmful. However, this study has impelled us not only to look at the strength and the significance outcomes of study and neglecting the trifle ones that may prime to serious healthcare consequences of the future society.